Validation and Quantification of Lead Detection in Water using Cysteine-functionalized Graphene/Polypyrrole Nanocomposite Film Electrode - (:unkn) unknown (My University, 2023)
This study introduces a novel lead detection sensor utilizing a composite of sGO/PPy for the precise identification of low lead concentrations in water. The developed sensor demonstrated successful identification and quantification of trace amounts of lead within the range of 13 to 17 ppb. Correlations between peak height, peak area, and specific lead concentrations were established, along with an exploration of temperature effects on peak characteristics. Real-world water samples, both unaltered and spiked, underwent effective testing for lead presence. The sensor exhibited promising outcomes, detecting lead in the proximity of 15 ppb and distinguishing compliance with EPA-mandated limits. Notably, its lightweight, portable design presents a practical alternative to bulky instruments traditionally employed in lead detection. The user-friendly nature eliminates the need for specialized personnel or expensive equipment, extending accessibility to a broad user base. The disposable lead sensor, utilizing Screen Printed Electrodes (SPEs), holds significant potential for cost-effective, on-site water sample analysis.